Studi Deskriptif tentang Kemampuan Mengingat Anak Usia 5-6 Tahun di Taman Kanak-Kanak Plus Marhamah Parupuk Tabing Padang - Mega Nanda; Rivda Yetti (Universitas Al-Hikmah Indonesia, 2019)
The reseacher looks at the ability to remember from several aspects that exist (taking note, accepting and producing). The research was motivated by the ability to remember children in the Kindergarten Plus Marhamah Parupuk Tabing Padang. The research used is descriptive research with a qualitative approach. To find out what the ability description is like remembering children aged 5-6 years in the Kindergarten Plus Marhamah Parupuk Tabing Padang. The subjects in thi study were children aged 5-6 year in class B1 of Marhamah Padang Kindergarten Plus. Informants from the study were the Marhamah Padang Kindergarten Plus teacher. Data collection techniques used in thi tudy are in the form of observation, interviews, and documentation. The data analyisis techniques follow Sugiyono’s steps, namely 1) data reduction; 2) data presentation; and 3) verification. The technique of validating the data in this study is in the form of a triangulation technique. The reults of thi study indicate that the aspect of ability to remember children aged 5-6 years in Kindergarten Plus Marhamah Parupuk Tabing Padang is well developed. 1) the enlightening aspect, it seems that children pay attention to the learning given by the teacher; 2) aspects of accepting, it seems that children can understand the contents of the leraning provided; 3) the aspect of producing, it is seen the the child is able to produce the work and explain the work to the teacher. The conclusion of this study is the ability to remember children aged 5-6 years in Kindergarten Plus Marhamah well developed seen through aspects of remembering (remembering, accepting, and producing)